Internalisasi Etika Bisnis Dalam Manajemen Sumber Daya Manusia - Rahayu, Sari (CV. ITTC INDONESIA, 2021)
Business Ethics is a way of conducting business activities that cover all aspects related to individuals, companies and society. The progress of an organization cannot be separated from the role of human resources supported by good ethics in each individual. The purpose of writing this journal is for the organization to function as a forum and a tool to achieve goals in which there are norms that must be guided and have values ​​that need to be adhered to. In terms of human resource management, ethics has an important role to ensure fair, effective and efficient action. Resource management is also responsible for the organization's efforts to deal with ethical behavior so that it can become a driving force in the organization and play a role in the development and training of the importance of improving employee morale.